Optimality Conditions for Approximate Pareto Minimality - Durea, Marius (Numerical functional analysis and optimization, 2020)
In this paper, we apply, to the case of approximate minimizers for vector optimization problems with set-valued maps, some techniques developed previously in literature for the situation of standard vector efficiency. The approach we propose here allows us, on one hand, to extend some known results, and, on the other hand, to emphasize some numerical aspects that could be of certain importance for scientific computation of approximate minima.